(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Processing food is necessary in order to preserve the quality, perfection, and efficiency of food production. Recent developments in machine learning techniques have brought about significant changes in the food processing industry. These changes have enabled real-time monitoring and control of a large number of processing parameters. This research studies the application of machine learning algorithms in the food processing business with the goals of increasing product quality, reducing waste, and ensuring compliance with standards governing food safety. The different methods and technologies that are deployed in the food processing industry are discussed in this research, along with the challenges that are encountered and the potential benefits that may be gained through integrating monitoring and control systems that are based on machine learning.